Representation of the Rules for Living in Personal Narratives of Adolescents with Hearing Impairments - Lytvynenko, Olena (Lesya Ukrainka Volyn National University, 2021)
The article is focused on the study of personal narratives of adolescents with hearing impairments. The aim of the study was to determine narrative indicators of respondents’ rules for living. To achieve this goal, there were analysed personal narratives of adolescents with hearing impairments. Besides, there were identified specific categories that reflect their rules for living. In addition, there was studied the level of subjective well-being of respondents and the relationship between the presentation of certain rules for living in personal narratives and the level of subjective satisfaction with life. The research methods were content analysis of personal narratives and subjective scaling. Statistical data processing was performed with the help of recursive division trees method. The results of the study show that rules for living typical for adolescents with hearing impairments are reflected in their narratives and can be divided into three groups. The first group includes self-focusing rules, the second – focusing on others, and the third – focusing on the out-world. Each of these groups is divided into two subgroups, and each subgroup includes the behaviour of supercompensation or avoidance. The most common among adolescents with hearing impairments are rules for living related to the focusing on others and self-focusing both by the type of avoidance. At the same time, the highest level of subjective satisfaction with life is connected with self-focusing rules for living by type of supercompensation. The obtained data allow us to conclude that the analysis of personal narratives of adolescents with hearing impairments allows to determine their rules for living. On the other hand, typical rules for living determine the level of person’s subjective well-being. Prospects for further researches in this area are to study the representation in adolescents’ narratives not only separate rules for living, but also core beliefs, the existence of which is ensured by these rules.
Keywords: personal narrative; content analysis; rules for living; core beliefs; adolescence; hearing impairments